Speech Acts in Mandarin Language Learning at a Junior High School: A Pragmatic Study - Asti ramadhani Sene; Arini Junaeny; Jufri A.P. (Universitas Negeri Semarang, 2026)
This study examines speech acts in teacher-student interactions during Mandarin language learning at Cheng Hoo Integrated Islamic Junior High School, Gowa, based on Searle's (1969) speech act theory. Using a qualitative descriptive method, Data were collected through observation, audio recording, and field notes during two learning sessions with ninth-grade students. Analysis of 170 utterances revealed that directive speech acts were most dominant (58 utterances), followed by representative (23), declarative (20), expressive (14), and commissive (6). Speech acts served three primary functions: conative (68 utterances) to encourage student action, cognitive (46 utterances) to transfer knowledge, and affective (27 utterances) to build motivation, with 44 utterances performing dual functions. The integrated Islamic school context demonstrated harmonious integration of Mandarin learning with religious values through multilingual practices involving Mandarin, Indonesian, and Arabic. These findings indicate that directive speech acts effectively manage classroom dynamics while representative acts support material delivery. The study contributes to pragmatic theory in foreign language education and provides practical implications for designing communication strategies in culturally responsive teaching environments.